PENERAPAN MODEL DISCOVERY LEARNING PADA MATERI EKOSISTEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA KELAS X SMA - Bhian Ananda Javanica Rubiyanto; Marjono Marjono; Baskoro Adi Prayitno (BIO-PEDAGOGI, 2016)
The research is aimed to improve higher order thinking skills students at class X IPA of SMA through the implementation of discovery learning model on the ecosystem subject. This research was a classroom action research which consists of two cycles. Each cycle contains four phases which were planning, acting, observing and reflecting. The subjects were students at class X IPA of SMA totaling 32 students. The data collecting techniques of this research were using test method obtained through essay test, and nontest method obtained through observation, interview, and documentation. The primary data is advanced higher order thinking skill of students with Bloom revised taxonomy to analyzing, evaluating, and creating measured using essays in accordance researchers any material indicators of ecosystem. The Data validate of this research were triangulation method. Analysis of data using qualitative descriptive analysis technique. The Target of research is to increase the higher order thinking skill’s students ≥25. The increase in higher order thinking skills results by the increasing student achievement of the average score of aspects of higher order thinking skills students were: 1)aspect analyzing of 52.66 with the moderate criteria of being at base line be 66.98 with the moderate criteria of being in the cycle I, then the the cycle II into 80,52 with a high criteria, 2)evaluating aspects of 45.83 with low criteria on base line be 64.17 with the moderate criteria of being in the cycle I, then on the cycle II into 73.96 with moderate criteria, and 3)creating aspects of 50,31 with the moderate criteria of being at base line be 68,49 with the moderate criteria of being in the cycle I, then on the cycle II into 76,35 with high criteria. Implication of discovery learning can increase the high order thinking skills students in base line, Cycle I and Cycle II. The score of test each aspect of higher order thinking skill aspect were: 1)analyzing increased by 27,86, 2)evaluating an increase of 28,13 from, and 3)creating increased by 26,04. This conclusion was implementation of discovery learning could improveas much as ≥25 of high order thinking skills students at class X IPA of SMA. Keywords : higher order thingking skill, discovery learning